PENGEMBANGAN PERANGKAT AJAR P5 TERINTEGRASI ETNOSAINS PADA PROSES PEMBUATAN KERUPUK PANGGANG MENGGUNAKAN ANYFLIP - Marbun, Forteen Kristina; Jufrida, Jufrida; Furqon, Muhamad (Lensa: Jurnal Kependidikan Fisika, 2025)
The Merdeka Curriculum’s Pancasila Student Profile Project (P5) seeks to integrate 21st-century competencies (collaboration, problem-solving, and digital literacy) within Indonesia’s pluralistic values. This study develops P5 teaching materials (a teacher’s companion book and a student module) that integrate ethnoscience by using Jambi’s kerupuk panggang production as a cultural context for heat and temperature. Using the ADDIE model, we conducted the development phase and produced a digital flipbook version via AnyFlip, then evaluated feasibility with qualitative and quantitative evidence from expert validators, teachers, and students. Expert reviews yielded mean feasibility scores of 81% for the companion book and 82% for the module (very good category). At the needs and perception stage, 42% of students reported understanding of local wisdom and its linkage to science concepts, and 63.3% indicated good motivation when learning was connected to P5. Teacher and student responses characterized the materials as practical and engaging for P5 activities. These findings support the feasibility and practicality of the materials for subsequent classroom implementation studies; effectiveness on learning outcomes was not tested in this phase.